2020
DOI: 10.1007/978-3-030-45231-5_32
|View full text |Cite
|
Sign up to set email alerts
|

The Polynomial Complexity of Vector Addition Systems with States

Abstract: Vector addition systems are an important model in theoretical computer science and have been used in a variety of areas. In this paper, we consider vector addition systems with states over a parameterized initial configuration. For these systems, we are interested in the standard notion of computational complexity, i.e., we want to understand the length of the longest trace for a fixed vector addition system with states depending on the size of the initial configuration. We show that the asymptotic complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…We also mention the quest for abstract program models whose resource bound analysis problem is decidable, and for which the obtainable resource bounds can be precisely characterised. We list here the size-change abstraction, whose worst-case complexity has been completely characterised as polynomial (with rational coefficients) (Colcombet et al, 2014;Zuleger, 2015), vector-addition systems (Brázdil et al, 2018;Zuleger, 2020), for which polynomial complexity can be decided, and LOOP programs (Ben-Amram and Hamilton, 2019), for which multivariate polynomial bounds can be computed. We are not aware of similar results for program models that induce logarithmic bounds.…”
Section: Related Workmentioning
confidence: 99%
“…We also mention the quest for abstract program models whose resource bound analysis problem is decidable, and for which the obtainable resource bounds can be precisely characterised. We list here the size-change abstraction, whose worst-case complexity has been completely characterised as polynomial (with rational coefficients) (Colcombet et al, 2014;Zuleger, 2015), vector-addition systems (Brázdil et al, 2018;Zuleger, 2020), for which polynomial complexity can be decided, and LOOP programs (Ben-Amram and Hamilton, 2019), for which multivariate polynomial bounds can be computed. We are not aware of similar results for program models that induce logarithmic bounds.…”
Section: Related Workmentioning
confidence: 99%
“…We also mention the quest for abstract program models whose resource bound analysis problem is decidable, and for which the obtainable resource bounds can be precisely characterised. We list here the size-change abstraction, whose worst-case complexity has been completely characterised as polynomial (with rational coefficients) [14,56], vector-addition systems [12,57], for which polynomial complexity can be decided, and LOOP programs [10], for which multivariate polynomial bounds can be computed. We are not aware of similar results for programs models that induce logarithmic bounds.…”
Section: Related Workmentioning
confidence: 99%
“…□ A natural question is whether Theorem 4.2 can be extended to other complexity classes such as O (𝑛 𝑘 ). Recall that the problem whether L A ∈ O (𝑛 𝑘 ) for a given demonic VASS A is decidable in polynomial time, and ifL A ∉ O (𝑛 𝑘 ), then L A ∈ Ω(𝑛 𝑘+1 )[20]. However, our proof of Theorem 4.2 requires G 𝑘 being closed under function composition, which does not hold for O (𝑛 𝑘 ) and 𝑘 ≥ 2.…”
mentioning
confidence: 97%
“…In the same paper, it is also shown that if L is not polynomial, then it is at least exponential, i.e., L ∈ 2 Ω (𝑛) . A recent result of [20] shows that if the termination complexity of a given demonic VASS is polynomial, then there is 𝑘 ∈ N computable in polynomial time such that L is Θ(𝑛 𝑘 ). A polynomial-time algorithm deciding the linearity of L for probabilistic VASS , i.e., VASS with demonic non-determinism and probabilistic choice 2 , is given in [2].…”
mentioning
confidence: 99%